Analisis Perbandingan Penggunaan Kali Linux pada Windows Subsystem for Linux (WSL) dan VirtualBox terhadap OpenSSL Benchmark Testing - Rheva Anindya Wijayanti; Rival Achmad Firdaus; Nathanael Berliano Novanka Putra; Aqwam Rosadi Kardian (Journal on Education, 2023)
In the context of the evolution of information technology, the integration of Linux operating systems within the Windows environment has become increasingly crucial. Windows Subsystem for Linux (WSL) and VirtualBox are two main approaches that offer solutions for running Linux on the Windows operating system. In the context of information security, performance testing of OpenSSL sign and verify becomes crucial. This research aims to compare the usage of each approach with a focus on the performance testing of OpenSSL sign and verify. The research method involves the implementation of the Phoronix Test Suite to measure the speed of Kali Linux in executing OpenSSL sign and verify within the WSL and VirtualBox environments. The results of the analysis indicate that in the OpenSSL sign and verify testing, WSL demonstrates superior performance compared to VirtualBox. WSL achieves faster execution times in running this test, suggesting that WSL can be a more effective choice in the context of performance, especially in tasks related to OpenSSL sign and verify. This research provides practical guidance for users aiming for maximum performance when running OpenSSL sign and verify tasks in the Kali Linux environment within the Windows operating system.